Menjembatani Cita-cita Syariah dan Realitas Sosial: Literasi, Kepercayaan Publik, dan Tantangan Perbankan Syariah di Indonesia - Ina Nasihatul Ummah; Ida Nurlaeli (ITB AAS INDONESIA Surakarta, 2026)
Islamic banking in Indonesia has experienced rapid growth since the establishment of Bank Muamalat in 1992; however, its market share remains relatively small compared to conventional banking. This condition raises questions regarding the gap between the ideality of Sharia principles grounded in maqasid al-shariah and the social reality characterized by low financial literacy, regulatory frameworks that are not yet fully adaptive, and fragile public trust. This study aims to analyze the problems of Islamic financial literacy, public trust, and regulation as the main factors influencing the development of Islamic banking in Indonesia. The research employs a qualitative literature review method with thematic analysis of previous studies published in both national and international journals. The findings indicate that low public literacy hinders Islamic financial inclusion, regulatory overlap with the conventional system creates uncertainty, and public trust is strongly influenced by transparency, efficiency, and product innovation. This article emphasizes the need for a comprehensive strategy encompassing the enhancement of Islamic financial literacy, regulatory harmonization, and the strengthening of product innovation so that Islamic banking can bridge the gap between Sharia ideality and social reality and contribute more significantly to national economic development. Novelty of this study lies in the development of a conceptual framework that bridges the ideals of Sharia with social realities through the integration of financial literacy, public trust, and regulatory policies. Its scientific contribution is the provision of a systemic perspective, emphasizing that the advancement of Islamic banking cannot rely solely on product expansion, but must be supported by financial literacy, regulatory consistency, and innovation grounded in maqasid al-shariah.